(3EOGQI GdJQhjL hGdGJUGdGJ (B/s - (3TdGT, YfHQ GHQGgjes ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2011)
(3GdGJUGdGJ aj GdGOGQI , YfGUQ GdeRjL GdJShjbj h echfGJ GdYedjI GdJShjbjI , GdGJUGdGJ GdJShjbjI hOhQ GdYedjI GdHjYjI ajgG , WHjYI Sdhc GdeSJgdc h CgejJg , JCKjQ KbGaI GdeLJeY Ydi Sdhc GdeSJgdc , OQGSI GdJQhjL cYedjI GJUGd , GdeRjL GdJQhjLj (B( (3eRjL GdGJUGd GdJShjbj(B) (3, GdGYdGf , NWhGJ GdHjY GdeHGTQ GdTNUj , eaghe h JWhQ h CgOGa GdYdGbGJ GdYGeI hhVGFagG h GdeTZhdhf HgGs
Keywords: (3COGQI GdeHjYGJs; (3GdEJUGds; (3GdJShjbs